A new family with transportinopathy: increased clinical heterogeneity. (June 2019) - Angelini, Corrado; Marozzo, Roberta; Pinzan, Elena; Pegoraro, Valentina; Molnar, Maria Judit; Torella, Annalaura; Nigro, Vincenzo
We describe a family with a novel TNPO3 mutation of limb–girdle muscular dystrophy D2 (or LGMD 1F), a rare muscle disorder with autosomal dominant inheritance, first identified in an Italo-Spanish family where the causative defect has been found to be due to TNPO3 gene mutation, encoding transportin-3 protein (TNPO3). We present the clinical, histopathological and muscle magnetic resonance imaging (MRI) features in two patients, mother and son Hungarian origin, affected by LGMD D2 and correlate their clinical, MRI and histopathological data found in this condition. The affected son presented early pelvic girdle muscle weakness and thin muscles similar to a congenital myopathy; the mother was less compromised and had an LGMD phenotype. Muscle MRI showed a very pronounced lower limb muscle atrophy in both patients. The most relevant change obtained in the child muscle biopsy was a generalized type 1 fibre atrophy. The two patients presented the same mutation, but a different phenotype has been observed in mother and son.